Factors Influencing Despair, Self-blame, and Acceptance Among Parents of Children with Autism Spectrum Disorder (ASD): A Malaysian Perspective - Muhammad Hanif, Abd Latif; Wan Salwina, Wan Ismail; Mohd Rizal, Abdul Manaf; Nur Iwana, Abdul Taib (Springer Nature, 2023)
Purpose Accepting and adapting to the child’s diagnosis of Autism Spectrum Disorder (ASD) can be challenging for parents. We aimed to assess domains of parental adjustment namely despair, self-blame, and acceptance among parents whose children were diagnosed with ASD. Methods A cross-sectional study was conducted among 111 parents of children with autism who attended Child and Adolescent Psychiatry Unit (CAPU), in a university teaching hospital in Kuala Lumpur, Malaysia. Sociodemographic profiles of both parents and children were gathered. Parental adjustment focusing on parental self-blame, despair and acceptance were assessed using self-reported questionnaires namely Adjustment to the Diagnosis of Autism (ADA). Results Higher level of despair was associated with parents who have medical illness (β=0.214, p=0.016) and children who received antipsychotic medications (β=0.329, p<0.001). Parents with tertiary education (β = -0.207, p=0.023) and those with autistic child attended school (β = -0.200, p=0.037) have lower level of despair. Parents with medical illness (β=0.245, p=0.008), child receiving antipsychotic medications (β=0.251, p=0.005), Chinese ethnicity (β=0.185, p=0.04), and child’s gender (β=0.283, p=0.003) were significantly associated with higher level of self-blame. Lower acceptance was found among Chinese parents (β = -0.264, p=0.005) while married parents had higher acceptance levels (β=0.215, p=0.022). Conclusion Parental adjustment involving domains of despair, self-blame, and acceptance were significantly associated with ethnicity of parents, educational level, parents’ marital status and medical illness, as well as the ASD children’s schooling status and type of medications used.